Isolation and Characterization of Bacterial Strains from Sea Water of Mandaicad in Tamil Nadu India - K R T Asha, Dr (International Journal of Pharmaceutical & Biological Archive, 2013)
Isolation and Characterization of Bacterial Strains from Sea Water of Mandaicad in Tamil Nadu India